A surrogate indicator of criticality for stochastic project networks - Tavares, Luís Valadares (2011)
The study of the delay that can be caused by any activity of a stochastic project network is a key topic because of the increasing importance of risk and time control in project management. The main concept adopted for this purpose has been the notion of critical activity developed for deterministic project networks but, in this paper, the inadequacy of the concept critical activity for stochastic project networks is shown and a new surrogate indicator of criticality (SIC) is built, using a regression model applied to a large set of generated project networks. This new indicator explains more than 90% of the initial variance estimated for more than 80,000 activities belonging to a wide range of project networks (580 nets), with very different morphological types.